Science Education Development in the Czech Republic since 1989 - Janoušková, Svatava; Teplý, Pavel; Čtrnáctová, Hana; Maršák, Jan (Scientia in educatione, 2019)
The Czech education system has been undergoing a number of essential changes during the past 30 years. After a long stagnation period of the centralized education system based on unified curricula for all schools, considerable transformation of the education system occurred in the 90´s. The reform focused on decentralization of the education system which enabled opening new schools and developing their own curricula gradually. Changes took place also in science education; a paradigm shift – mostly due to the new educational system open for new global science educational trends – can be recognized. The article aim is mapping approaches and attitudes towards science education in the past 30 years. Strategic and conceptual documents of the Ministry of Education (e.g. long-term educational goals and goals of educational system development; government education strategy as well as particular strategies related to science education) and other documents drafted by organizations as e.g. the Research Institute of Education (nowadays the National Institute for Education, Education Counselling Centre and Centre for Continuing Education of Teachers) and the Czech School Inspectorate will be examined by a thematic qualitative analysis. Based on the findings, we intend presenting a broader context of the science education. In the second part of the article we focus on changes in goals for science education by analyzing the target orientation of science education curricula since 1989. Also, we intend focusing on inclusion of alternative methods and approaches into science education curricula. An appropriate selection of documents to be analyzed and their objective interpretation will be secured by the composition of the authors team who were involved in many reform measures directly or as advisers and therefore they may enrich the analysis by bringing an expert view.